Analisis Pengaruh Tingkat Pendidikan, Umur, dan Keterampilan Terhadap Waktu Tunggu Bekerja Bagi Tenaga Kerja Terdidik di Kecamatan Selong Kabupaten Lombok Timur - Martini, Baiq Julyan Dwianti; Wahidin, Wahidin; Handayani, Tuti (Laboratorium Riset Ekonomi, 2024)
Research with the title Analysis of the Influence of Education Level, Age and Skills on Waiting Time to Work for Educated Workers in Selong District, East Lombok Regency with the aim of analyzing how much influence the level of education, age and skills have on waiting time to work for educated workers in the District Selong, East Lombok Regency. The results of the research can be concluded that the education level variable and the skills variable have a negative and significant effect on the waiting time for educated workers in Selong District, East Lombok Regency. The age variable has a positive and significant effect on the waiting time for educated workers in Selong District, East Lombok Regency. The variables of education level, age and skills together have a positive or negative and significant effect on the waiting time for educated workers in Selong District, East Lombok Regency. Key Words: Education Level, Age, Skills, Waiting Time to Work